Timing of Adjunctive Azithromycin for Unscheduled Cesarean Delivery and Postdelivery Infection. Issue 6 (2nd June 2022) - Sanusi, Ayodeji; Ye, Yuanfan; Boggess, Kim; Saade, George; Longo, Sherri; Clark, Erin; Esplin, Sean; Cleary, Kirsten; Wapner, Ron; Owens, Michelle; Blackwell, Sean; Szychowski, Jeff M.; et al.
Abstract : In patients undergoing unscheduled cesarean delivery, adjunctive azithromycin administration up to 60 minutes before or at a median of 3 minutes after skin incision was associated with reduced risks of postoperative infection. Abstract : OBJECTIVE: To estimate the association between timing of administration of adjunctive azithromycin for prophylaxis at unscheduled cesarean delivery and maternal infection and neonatal morbidity. METHODS: We conducted a secondary analysis of a randomized trial of adjunctive azithromycin prophylaxis in patients with singleton gestations who were undergoing unscheduled cesarean delivery. The primary exposure was the timing of initiation of the study drug (after skin incision or 0–30 minutes, more than 30–60 minutes, or more than 60 minutes before skin incision). The primary outcome was a composite of endometritis, wound infection, and other maternal infections occurring up to 6 weeks after cesarean delivery. Secondary outcomes included composite neonatal morbidity, neonatal intensive care unit admission for longer than 72 hours, and neonatal sepsis. The association of azithromycin with outcomes was compared within each antibiotic timing group and presented as risk ratios (RRs) with 95% CIs. A Breslow-Day homogeneity test was applied to assess differences in association by antibiotic timing. RESULTS: Of 2, 013 participants, antibiotics were initiated after skin incision (median 3 minutes, range 0–229 minutes) in 269 (13.4%), 0–30 minutes before skin incision in 1, 378 (68.5%), more than 30–60 minutes before skin incision in 270 (13.4%), and more than 60 minutes before skin incision (median 85 minutes, range 61–218 minutes) in 96 (4.8%). The RRs (95% CIs) of the infectious composite outcome for azithromycin compared with placebo were significantly lower for groups that initiated azithromycin after skin incision or within 1 hour before skin incision (after skin incision: RR 0.31, 95% CI 0.13–0.76; 0–30 minutes before: RR 0.62, 95% CI 0.44–0.89; more than 30–60 minutes before: 0.31, 95% CI 0.13–0.66). Risks were not significantly different in patients who received azithromycin more than 60 minutes before skin incision (RR 0.59, 95% CI 0.10–3.36). Results were similar when endometritis and wound infections were analyzed separately. Neonatal outcomes were not significantly different for azithromycin compared with placebo across all timing groups. CONCLUSION: Adjunctive azithromycin administration up to 60 minutes before or at a median of 3 minutes after skin incision was associated with reduced risks of maternal composite postoperative infection in unscheduled cesarean deliveries. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01235546.